Kajian Teoritis Pengembangan Model Keberhasilan Sistem ERP - Victor O. Lawalata; D. B. Paillin (Industrial Engineering Study Program, Pattimura University, 2011)
Even ERP systems success was modeled with considering for various aspects; the contribution of contingency factors has not been had a well-structure. Investigation by Ifinedo (2007) introduced a new relation model between organization characteristics (contingency factor) and ERP systems success by moderating of IT organizational factors (IT assets dan IT resources). This model involves only 3 characteristics, namely size, structure and culture of organization. Referred to the reference study on number of pre-related researches, there are connections between all organization characteristics (size, structure, culture, strategies and environment of organization) and ERP systems success by moderating of IT organizational factors. Our research provides a theoretical review to develop an ERP systems success and cross-relational hypothesizes of variables according to previous researches.